Effect of Feeding Rice Distillers Dried Grains and Mixture of Non-legume and Legume Straw on Hemato-Biochemical and Mineral Profile of Growing Dairy Heifers - Pandey, Manish; Shah, S.V.; Trivedi, M.M.; Pathan, M.M.; Lunagariya, P.M.; Patel, Y.G. (Indian Journal of Animal Nutrition, 2022)
Under scarcity of livestock feeds and fodder, an investigation on alternate, conventional and nonconventionalfeed resources is essential. The present study was planned on crossbred heifers (HF×Kankrej)with average body weight of 116.1±4.74 kg for twelve fortnights to study the effect of feeding riceDDGS and a combination of straw (wheat + groundnut) on their hemato-biochemical and mineral profile.Blood samples for hemato-biochemical and mineral profile analysis were collected from heifers atthe start of the experiment and thereafter at every fortnightly interval from the jugular vein in the sterilizedblood collecting tubes (with and without anticoagulant). Auto-hematology-analyzer Mindray (BC-2800Vet) and Mindray BS-120 chemistry analyzer were used for hematology and serum biochemistryanalysis, respectively. The RBC counts, Hb, PCV%, MCHC, Platelet count, MPV, WBCs and Granulocyteschanged significantly (P